(untitled) (Research, Society and Development, 2020)
Alcohol use disorders are among the most prevalent mental disorders in Brazil and worldwide. This substance is related to the low bioavailability of some important nutrients. In this sense, the present study aimed to relate the impairment in the absorption of nutrients with alcohol consumption. This is a simple literature review, with a search for the topic in databases and analysis of articles from the last 19 years. It has been observed that alcohol can impair intestinal absorption and increase renal excretion of folate. Some vitamins like vitamin A and C, B6, niacin have their absorption impaired by alcohol consumption. The deficiency of some vitamins and minerals, such as some of the complex B and magnesium, mineral that plays a crucial role in various reactions of the body. In this way, it was observed that the ingestion of alcohol, especially regular alcohol, has a direct association with losses in bioavailability and nutrient absorption.